Study of electrical properties of poly-3-alkylthiophen (P3AT) derivatives P3HT, P3BT and P3DDT based field effect transistors - Tiwari S.; Tiwari S.; Prakash R.; Balasubramanian S.K. (My University, 2025)
Top contact organic thin-film field effect transistors based on regioregular poly(3-butylthiophene-2,5-diyl) (P3BT), poly(3-dodecylthiophene-2, 5-diyl) (P3DDT) and poly(3-hexylthiophene-2,5-diyl) (P3HT) of similar concentration were fabricated by spin coating technique. The current-voltage (I-V) characteristics of these three different polymer based organic field-effect transistors (OFETs) were studied. The device performance parameters for each kind of OFET were estimated with the help of measured electrical characteristics and performance were compared to optimize the best polymer for FETs amongst these three polymers. © 2013 IEEE.